Предмет: Алгебра,
автор: luda540
40 баллов, нужно решение только 1, пожалуйста
Приложения:
Ответы
Автор ответа:
0
Решение
1) [√(6 - √11) + √(6 + √11)]² = [√(6 - √11)]² + 2*√(6 - √11)*(6 + √11) + [√(6 + √11)]² =
= 6 - √11 + 2*√(36 - 11) + 6 + √11 = 12 + 2*√25 = 12 + 2*5 = 12 + 10 = 22
2) √(36 + 12x + x²) = √(6 + x)² = I 6 + x I
1) [√(6 - √11) + √(6 + √11)]² = [√(6 - √11)]² + 2*√(6 - √11)*(6 + √11) + [√(6 + √11)]² =
= 6 - √11 + 2*√(36 - 11) + 6 + √11 = 12 + 2*√25 = 12 + 2*5 = 12 + 10 = 22
2) √(36 + 12x + x²) = √(6 + x)² = I 6 + x I
Похожие вопросы
Предмет: Математика,
автор: keshkerekuru
Предмет: Математика,
автор: gulnaraorucova74
Предмет: Алгебра,
автор: gamedzover
Предмет: Обществознание,
автор: KbyfKbyfKbyf